Membaca Tantangan Kerukunan Antaragama di Indonesia - Hisyam, Mohamad Ali; Kamaruddin, Wan Zailan (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2015)
The article briefly maps and analyzes a number of obstacles in creating interreligious harmony in Indonesia. It also offers potential solutions to be practically implemented. The writers observe that there are a number of problems which become obstacles to build interreligious harmony such as economic and political problems, dispute over territory, the difference of ideological doctrines, role of the mass media, provocative and unfair (biased) journalism, and the clash among religious missionaries of each religion when they encounter one with another in the field. In the last part of the article the writers provides an illustration on how interreligious harmony has been impressively implemented in Bali. The writers argue that interreligious life in Bali is a robust example for interreligious harmony. In addition, a number of experts consider the dynamic of interreligious life in Bali a remarkable model of how social harmony is well managed within a plural society. One may assume that Bali is an ideal miniature of interreligious harmony in Indonesia. Therefore, it should be imitated and implemented in other regions of our country.